Where There Are Asians, There Are Rice Cookers : How "National" Went Global via Hong Kong - Nakano, Yoshiko, 1964- (Book collections on Project MUSE., 2009)
This is the first English-language book to focus on the electric rice cooker and the impact it has had on the lives of Asian people.